Effect of Change Contract Order, Labor, Material, Tools to Time Delayu of Low-Rise State Building Project - Tobing, Pahala R; Suroso, Agus (ASTONJADRO, 2025)
Construction of state low-rise buildings in Pangkalpinang city is a common project that usually built by The Public Works Department of Pangkalpinang. The problem often faced by construction of state low-rise buildings projects at Pangkalpinang is the low performance of time (Delay). This condition be expected caused by Change Contract Order (CCO), man power, materials, and machine, This research aims to analyze the influence of those factors on delay time in state low-rise building construction projects. The analysis used in this research is multiple regression with SPSS. This research find that both and parsially the 4 (four) factors influence the time-performance (delay) of low-rise state building construction. Based on data analysis, the equation Y = 3.887+ 0.390 X1 + 0,278 X2 + 0,265 X3 + 0,341 X4. Based on the results of the Coefficient of Determination Test, simultaneously CCO Factors (X1), Manpower Factors (X2), Materials Factors (X3) and Machines Factors (X4) have an influence contribution of 74.0 % of Time Performance (Y). Meanwhile, for the results of the most dominant factor analysis using Beta Standardized x Zero-Order, it was found that the CCO Factor (X2) was the most dominant factor that could influence time performance with an influence value of 23.99%. Considerations in determining alternative solutions to control time performance in state low-rise building construction projects are carried out on the most dominant factor, namely the CCO Factor (X1).